2012
DOI: 10.1371/journal.pone.0045844
|View full text |Cite
|
Sign up to set email alerts
|

Specific Silencing of the REST Target Genes in Insulin-Secreting Cells Uncovers Their Participation in Beta Cell Survival

Abstract: The absence of the transcriptional repressor RE-1 Silencing Transcription Factor (REST) in insulin-secreting beta cells is a major cue for the specific expression of a large number of genes. These REST target genes were largely ascribed to a function of neurotransmission in a neuronal context, whereas their role in pancreatic beta cells has been poorly explored. To identify their functional significance, we have generated transgenic mice expressing REST in beta cells (RIP-REST mice), and previously discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…This led to a decrease in the number of endocrine-committed progenitors by E14.5 and ultimately reduced the numbers of glucagon + and insulin + cells in E18.5 pancreas. Eventually, adult mice developed diabetes, an observation that we already made in RIP-REST mice overexpressing REST specifically in beta cells (Martin et al, 2012). Diabetes in Pdx1-tTA/TetO-REST mice is most likely caused by an impaired function, rather than being caused by the moderate reduction in insulin-producing cells.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This led to a decrease in the number of endocrine-committed progenitors by E14.5 and ultimately reduced the numbers of glucagon + and insulin + cells in E18.5 pancreas. Eventually, adult mice developed diabetes, an observation that we already made in RIP-REST mice overexpressing REST specifically in beta cells (Martin et al, 2012). Diabetes in Pdx1-tTA/TetO-REST mice is most likely caused by an impaired function, rather than being caused by the moderate reduction in insulin-producing cells.…”
Section: Discussionmentioning
confidence: 87%
“…By analyzing a new RIP-REST founder line, we further showed that higher levels of REST trans-gene expression drastically compromised beta cell survival, leading to diabetes (Martin et al, 2012). Here, we report the same impairment in glucose homeostasis with another transgenic system driving REST expression in adult mature beta cells (under the control of Pdx1 regulatory region) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations